A Curadoria de dados científicos na ciência da informação: levantamento do cenário nacional - Liliane Chaves de Resende (2019)
For contemporary science, data sharing is a key element for its progress and collaboration among scientific communities. In the context of open science and e-science, information science and the information professional seek solutions to the challenges of handling and better use of information, specifically with respect to digital curation activities for research data. The current lack of knowledge of digital curation of scientific data and the degree of adherence to this new scenario brings increasing difficulties for the information professional to adapt in this context and contribute solutions to the challenges of digital curation. The objective of this research is to investigate the importance that the digital curation activities of scientific data have for the area of Information Science in Brazil, in face of the international trend of scientific knowledge management. The research follows quantitative approach, is applied in nature, exploratory, and descriptive. Procedures are used for a quasi-systematic literature review, to obtain an overview of Digital Curatorship in the international scope, and a survey with Survey, to obtain information from Digital Curatorship through the opinion of Brazilian researchers in the area of Information Science. The information analyzed reveals that the field of Brazilian Information Science is seeking to adapt in this scenario. Investigating the trends of the world scenario of Digital Data Curation activities and how these activities are performed by Brazilian researchers will provide support for the development of the Information Science area in Brazil.